Accurate quantitation of D+ fetomaternal hemorrhage by flow cytometry using a novel reagent to eliminate granulocytes from analysis. Issue 5 (17th November 2013) - Kumpel, Belinda; Hazell, Matthew; Guest, Alan; Dixey, Jonathan; Mushens, Rosey; Bishop, Debbie; Wreford‐Bush, Tim; Lee, Edmond
<x xml:space="preserve">Abstract</x> Background Quantitation of fetomaternal hemorrhage (FMH) is performed to determine the dose of prophylactic anti‐D (RhIG) required to prevent D immunization of D– women. Flow cytometry (FC) is the most accurate method. However, maternal white blood cells (WBCs) can give high background by binding anti‐D nonspecifically, compromising accuracy. Study Design and Methods Maternal blood samples (69) were sent for FC quantitation of FMH after positive Kleihauer‐Betke test (KBT) analysis and RhIG administration. Reagents used were BRAD‐3–fluorescein isothiocyanate (FITC; anti‐D), AEVZ5.3‐FITC (anti–varicella zoster [anti‐VZ], negative control), anti‐fetal hemoglobin (HbF)‐FITC, blended two‐color reagents, BRAD‐3‐FITC/anti‐CD45‐phycoerythrin (PE; anti‐D/L), and BRAD‐3‐FITC/anti‐CD66b‐PE (anti‐D/G). PE‐positive WBCs were eliminated from analysis by gating. Full blood counts were performed on maternal samples and female donors. Results Elevated numbers of neutrophils were present in 80% of patients. Red blood cell (RBC) indices varied widely in maternal blood. D+ FMH values obtained with anti‐D/L, anti‐D/G, and anti‐HbF‐FITC were very similar (r = 0.99, p < 0.001). Correlation between KBT and anti‐HbF‐FITC FMH results was low (r = 0.716). Inaccurate FMH quantitation using the current method (anti‐D minus anti‐VZ) occurred with 71% samples having less than 15 mL of D+ FMH (RBCs) and insufficient RhIG calculated for 9%. Using two‐color reagents and anti‐HbF‐FITC, approximately 30% patients had elevated F cells, 26% had no fetal cells, 6% had D– FMH, 26% had 4 to 15 mL of D+ FMH, and 12% patients had more than 15 mL of D+ FMH (RBCs) requiring more than 300 μg of RhIG. Conclusion Without accurate quantitation of D+ FMH by FC, some women would receive inappropriate or inadequate anti‐D prophylaxis. The latter may be at risk of immunization leading to hemolytic disease of the newborn.